Automatic formation of electron transport layer in BHJ solar cells using phenothiazine-based conjugated small molecular electrolytes. Issue 40 (26th September 2022) - Meng, LingXin; Kim, Danbi; Yang, Eunhye; Suh, Hongsuk; Park, Sung Heum
Abstract : We report the design and synthesis of phenothiazine-based conjugated small-molecular electrolytes as an ETL that could be applied to provide spontaneous phase separation, to reduce the number of steps required for device fabrication. Abstract : Phenothiazine-based conjugated small-molecular electrolytes (CSMEs) with different numbers of amine groups were designed and synthesized. CSMEs are used to form an electron transport layer (ETL) via spontaneous phase separation in bulk-heterojunction (BHJ) solar cells. During the device fabrication process, a mixed solution of CSME and BHJ photoactive layer materials is coated on top of indium tin oxide (ITO), and a thin layer of CSME, which plays the role of an ETL, is automatically formed between the active layer and ITO, as confirmed by high-resolution Time-of-Flight Secondary Ion Mass Spectrometry (TOF-SIMS). The power conversion efficiencies (PCEs) of the BHJ solar cells increased from PzN1 to PzN3 upon the increase in the number of amine groups. However, the introduction of the four amine groups in PzN4 decreased the PCE. PzN3 with three amine groups exhibited the best PCE value of 5.45% without using any other ETL materials. In contrast, the reference device with no ETL materials and CSMEs exhibited very poor performance, with a PCE of 0.4%. This study provides new strategies for the design of ETL molecules that can reduce the number of processing steps required for device fabrication.